Identity undoing and power relations in leadership development. (September 2013) - Nicholson, Helen; Carroll, Brigid
Leadership development theory and practice is increasingly turning its gaze on identity as a primary focus for development efforts. Most of this literature focuses on how the identities of participants are strengthened, repaired and evolved. This article focuses on identity work practices that are underdeveloped in the literature: the deconstruction, unravelling and letting go that can be experienced when working upon one's self. We group these experiences, among others, under the conceptual term 'identity undoing' and, based on findings from an 18-month ethnographic study of a leadership development program, we offer five manifestations of how it can be experienced. Through foregrounding the undoing of identity, we are able to look more closely at how power relations shape the leadership development experience. In order to raise questions and propositions for leadership and its development we use a micro-sociological and interactionist approach to explore the interplay between identity and power.